2018
DOI: 10.1097/md.0000000000010484
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the impact of test-and-treat strategies on hepatitis B virus infection in China by using an age-structured mathematical model

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
(62 reference statements)
1
11
0
Order By: Relevance
“…389,390 Future efforts to reduce hepatitis-related morbidity and mortality in China should focus on preventive strategies, safe blood practices, public education, and training health staff for large-scale HBV and HCV testing and treatment provision. 391 A strict action plan to reduce the harmful use of alcohol such as an excise tax on beer, wine, and spirits, and legally binding regulations on alcohol advertising should be implemented. The Government should also implement an operational policy to reduce unhealthy dietary practices and promote physical activity to prevent NAFLD.…”
Section: Priorities To Address the Burden Of Liver Diseases In The Asmentioning
confidence: 99%
“…389,390 Future efforts to reduce hepatitis-related morbidity and mortality in China should focus on preventive strategies, safe blood practices, public education, and training health staff for large-scale HBV and HCV testing and treatment provision. 391 A strict action plan to reduce the harmful use of alcohol such as an excise tax on beer, wine, and spirits, and legally binding regulations on alcohol advertising should be implemented. The Government should also implement an operational policy to reduce unhealthy dietary practices and promote physical activity to prevent NAFLD.…”
Section: Priorities To Address the Burden Of Liver Diseases In The Asmentioning
confidence: 99%
“…Several previous HBV modeling studies have evaluated the epidemiology of chronic HBV infection in China [ 17 19 ]. Those studies found that increased screening and treatment were effective in reducing chronic HBV infection, and enhanced vaccination was beneficial in eliminating transmission.…”
Section: Introductionmentioning
confidence: 99%
“…According to the POLARIS modeling study, in the mainland of China, only around 20% of those chronically infected with HBV were actually diagnosed and and 10% of those who were eligible to be treated received treatment (45). Investment case modeling studies suggested that if we only treat the few millions of CHB who are already on the treatment, the HBV-related cirrhosis/HCC mortality will still be increasing over the next two decades; on the other hand, if we scale up test-and-treatment strategies and treat most or even all persons who need the treatment, the HBV-associated mortality will dramatically decline, which is cost-effective or even cost-saving (46). For example, if the treatment coverage increased from current practice (12.5%) to 100% from 2018, the numbers of chronic HBV infections, new HBV infections, and HBV-related deaths in 2035 would be reduced by 26.60%, 24.88%, and 26.55%, respectively, and in 2050, it would be reduced by 44.93%, 43.29%, and 43.67%, respectively (47).…”
Section: Perspective On the Massive Test-and-treat Strategymentioning
confidence: 99%